Revitalizing an Asset-Based Cultural Economy: Empowering MSMEs in the Balla Barakka ri Galesong Area Through an Asset-Based Community Development Approach - Jaya, Asri; Khaliq, Abd.; Sahrullah, Sahrullah; Nurlina, Nurlina (Journal of Community Service and Society Empowerment, 2026)
Rural economic empowerment increasingly faces a gap between strong cultural potential and limited managerial capacity to respond to global markets. In Galesong Kota Village, Takalar Regency, this is evident in the Balla Barakka ri Galesong customary settlement, where rich historical-cultural assets remain stagnant due to passive management and weak integration into a modern business ecosystem. The challenge is reinforced by limited cross-generational synergy, with MSMEs relying on traditional practices while youth creativity is underutilized. This community service program aimed to overcome stagnation by strengthening MSME economic independence, promoting sustainable well-being, and building collaboration among artisans, youth, and POKDARWIS to support the “Impact Village” vision. Implemented through the Asset-Based Community Development (ABCD) approach, the program shifted participants toward an asset-oriented mindset. Conducted participatorily on October 5, 2025, with 50 participants, it used asset mapping and appreciative inquiry via workshops and FGDs to identify “hidden treasures” and design strategies that transform cultural value into economic value without undermining sacred traditions. Results were highly significant, shown by a 97% increase in understanding of business management and asset development. The program also produced functional integration: Balla Barakka’s historical narrative became the core value proposition of MSME products, while older generations safeguarded authentic production quality and younger generations led digital marketing and packaging innovation. Overall, ABCD proved effective in revitalizing the village economy by turning passive assets into productive capital through inclusive collaboration.